Exploring the role of sustainable logistics service providers in multinational supply chain cooperation: An integrated theory-based perspective - Su, Miao; Fang, Mingjie; Pang, Qiwei; Park, Keun-sik (Frontiers in Environmental Science, 2022)
There is a dearth of empirical studies on the impact mechanism of multinational logistics service providers’ sustainable practices on developing nations’ suppliers of sustainable production and competitive advantage in the context of supply chain cooperation. This study applies contingency theory, innovation diffusion theory, and resource advantage theory to examine the impact of logistics service providers on the sustainable production and competitive advantage of suppliers in developing countries in the context of multinational supply chain cooperation (MSCC). We received feedback from 215 suppliers in China and used structural equation modeling to analyze and discuss hypothetical models. This study suggests that logistics service providers' sustainable practices are a significant element influencing the establishment of MSCC. Implementing five-stage collaboration methods based on innovation diffusion theory, including knowledge exchange, persuasion, decision-making, execution, and confirmation, during the MSCC process will result in a stronger sustainable production effect and competitive advantage in developing countries